Perbandingan Efektivitas Pemberian Madu Randu dan Sari Kurma terhadap Peningkatan Nafsu Makan Balita Stunting - Devie Ismayanty; Rif’atul Mahmudah; Evi Avicenna (Faletehan Health Journal, 2025)
One in five children under 5 years old do not grow well due to malnutrition. This condition can be overcome by giving randu honey and date juice. Honey can help with nutrient absorption, while dates have a balanced nutritional composition. This study aimed to compare the effectiveness of randu honey (Ceiba pentandra) and date juice in increasing the appetite of malnourished toddlers. The research design is pre-experimental with a two-group pre-test-post-test design. Purposive sampling was used to select 20 toddlers diagnosed with malnutrition. Data were analyzed using the paired sample t-test. Instruments included observation sheets, the Children’s Eating Behavior Questionnaire (CEBQ), and checklists. The increase in appetite had a higher mean difference in the date juice group compared to the randu honey group, which was 19.40±25.10 with a p value of 0.006. This indicates a difference in appetite increase between the randu honey and date juice intervention groups. This study recommends that toddlers should be given natural ingredients such as date juice to increase their appetite.